Needs Assessment in Parents of Children Affected by Cancer: A Qualitative Perspective - Blanca Bretones Nieto; Carmen Pozo Muñoz; María Ángeles Vázquez López (MDPI AG, 2022)
Background: Childhood cancer is a "stressful experience" for parents in their role as caregivers. The aim of this study is to analyze the needs of a group of parents who have children diagnosed with cancer. The assessment looks at all areas of their daily life using a qualitative content analysis approach. Methods: This study uses open questions designed to investigate the main problems faced by the parents of children with cancer. All the answers were analyzed using MAXQDA 20 software. The study was conducted according to the Consolidated Criteria for Reporting Qualitative Research (COREQ). Results: The content analysis of the answers from 13 mothers and 7 fathers is presented. The main themes as priority areas of need were: "informal social support", "coping", "stressors/imbalances" and "health problems". Dissatisfaction with the support provided from the informal network was detected. Although the participants expressed active coping, they also exhibited helplessness, as well as concerns regarding possible sequelae and the impact of this situation on the family's economic/work context. Conciliation problems were a source of stress. All this is consistent with the participants suffering from a variety of health issues. Conclusions: the results show the effect of childhood cancer on different aspects of family life. They provide essential information for designing psychosocial interventions.